First results from third harmonic ion cyclotron acceleration of deuterium beams in EAST ion heating studies experiments. (1st March 2023) - Zhu, G.; Zhang, W.; Zhang, X.; Zhong, G.; Qin, C.; Liu, L.; Yang, H.; Liao, L.; Cheng, Y.; Mao, Y.; Yuan, S.; Wang, Y.; et al.
Abstract: Recent Experimental Advanced Superconductivity Tokamak experiments have been dedicated to the studies of increasing ion temperature using Neutral Beam Injection (NBI) in synergy with radio-frequency waves in the Ion Cyclotron Range of Frequencies (ICRFs) in third harmonic. They showed that this scenario effectively accelerates fast deuterium ions and produces a larger tail of fast neutrons with E > 3.0 MeV, as measured by Neutron Energy Spectrum. Comparing to the scenario with 2.2 MW NBI alone, adding an addition of 0.3 MW ICRF power leads to an enhancement of fusion yield by 67% (from 0 .73 × 1 0 14 n s − 1 to 1 .22 × 1 0 14 n s − 1 ) and an increase of core ion temperature by Δ T i ∼ 7 80 eV . Besides, the simulation results of TRANSP show that the neutron yield produced by 0.2 MW ICRF in third harmonic with NBI synergy is roughly consistent with the experimental results. Meanwhile, the 80 keV fast ion tail generated by NBI can be heated up to 400 keV and 600 keV by the 0.2 MW and 1.0 MW ICRF with the synergistic effect, respectively. In addition, it is observed for the first time that this ICRF-NBI synergy leads to the excitation of fishbone instabilities with characteristic frequencies of (10–20) kHz. Furthermore, parameter scans of ICRF/NBI power and plasma density were performed for third harmonic ICRF and NBI synergetic heating schemes. It is found that the neutron yield increases nonlinearly as the ICRF power or plasma density increases.